Development of emphatic catalysts for waste water remediation via synchronized free radical and non-free radical routes with composites of strontium hexaferrite, graphene and multi-walled carbon nanotubes. Issue 4 (15th February 2022) - Kaur, Paramdeep; Singh, Sneha; Renu,; Jyoti,; Kumar, Vinod; Tikoo, K.B.; Kaushik, Anupama; Singhal, Sonal
Abstract: Magnetic nanoparticles have shown exceptional potential in catalysis, however, their tendency to agglomerate has confined their use. The present work encompasses synthesis of eco-friendly and magnetic retrievable catalysts with different fractions of reduced graphene oxide (rGO) and multiwalled carbon nanotubes (MWCNT) as support for strontium hexaferrite (SrFe12 O19 ) for the oxidative degradation of organic pollutants. The morphological, structural and magnetic properties of composites were estimated via PXRD, FT-IR, VSM, FE-SEM, HR-TEM, XPS and BET. The crystallite size decreased from 41.46 nm for SrFe12 O19 to 35.85 nm and 33 nm for composites with 20% rGO and MWCNTs, respectively while the surface area increased substantially from 88.1 m 2 /g for SrFe12 O19 to 118.4 and 131.3 m 2 /g. Further, the composites were employed as catalysts for the oxidative degradation of selected antibiotics and colourant via stimulation of two different oxidants, potassium peroxymonosulphate (PMS) and hydrogen peroxide (H2 O2 ). The degradation followed pseudo first order kinetics with rate constant values increasing with rGO and MWCNT content. The increase in catalyst effectiveness can be ascribed to the synergistic interactions between rGO or MWCNT and SrFe12 O19, which provided larger specific surface areas for adsorption and augmented number of catalytically active sites. Systematic chemical quenching studies unveiled a combined role of radical and non-radical species in oxidative degradation of pollutants. Moreover, the synthesized composites exhibited excellent recyclability upto four cycles forming the basis for their utilization as industrial catalysts.